2010
DOI: 10.1007/s11695-010-0224-x
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Process in Post-bariatric Patients: an Experimental Evaluation

Abstract: Bariatric surgery is the most effective treatment for morbid obesity. Despite this, side effects are recorded. One of them is redundant skin hanging from the patients' body causing both aesthetical and functional deformities. They can only be corrected with body contouring surgery, whose wound complication rate is very high in previously obese population. Despite several hypotheses, an adequate explanation is still awaited. The aim of our study was to evaluate the wound healing process in post-bariatric patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 52 publications
(52 reference statements)
0
21
0
2
Order By: Relevance
“…However, despite preoperative nutrient replacement, increased rates of wound complications have been reported in this population [15]. Thus, it is possible that other mechanisms, such as high mechanical stress on tissues before bariatric surgery or weight loss, may also lead to poor healing because of decreased tissue elasticity and impaired microcirculation [15,16].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, despite preoperative nutrient replacement, increased rates of wound complications have been reported in this population [15]. Thus, it is possible that other mechanisms, such as high mechanical stress on tissues before bariatric surgery or weight loss, may also lead to poor healing because of decreased tissue elasticity and impaired microcirculation [15,16].…”
Section: Discussionmentioning
confidence: 98%
“…The impact of bariatric surgery on wound healing has been well studied in elective body-contouring surgery after weight loss [14][15][16]. One potential hypothesis is that poor wound healing in these patients is attributable to nutrient deficiencies, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, due to the worldwide growth of obesity [4] and of bariatric surgery [5], the number of ex-obese individuals who undergo plastic surgery has increased, thereby requiring special attention in the field of plastic surgery [6,7]. The number of post-operative complications tends to be higher in patients with a history of morbid obesity; although the true causes of these complications are still under investigation [8], health care professionals need to give post-bariatric patients special care [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent histological and molecular studies have confirmed that the abdominal dermis of the morbidly ex-obese shows lymphocytic infiltrations and destructuration of the collagen and elastic network [8,10,11], a lower quantity of heparan sulfate, and lower genetic expression of perlecan and type III collagen [12]. The destructuration of the fibrous extracellular matrix of the dermis is more intense in the infra-umbilical (IU) region [13].…”
Section: Introductionmentioning
confidence: 99%